2008
DOI: 10.14507/epaa.v16n9.2008
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' response to standards-based reform: Probing reform assumptions in Washington State.

Abstract: Because teachers' efforts are central to the success of standards-based reform, it behooves the policy community to look carefully at the beliefs about instruction that are rooted in this reform theory. Building on teacher-centric research on standards-based reform and ideas about teaching practice from research on multicultural education, this paper focuses on the assumptions embedded in Washington state's approach. Survey data from a representative sample of teachers suggest that the state's program of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Moreover, they believe the time they have to prepare students for the CCAA-WL is inadequate, PD efforts have been insufficient to help them understand the measurement properties of the assessments and how to use test data to identify students' writing strengths and needs, and support from administrators to use test data to improve classroom writing instruction is lacking. Our findings comport with other surveys that report negative attitudes toward assessments (Lyons, 2014), often because they are viewed as subtractive rather than additive elements in the education system (also see Loeb, Knapp, & Elfers, 2008), especially when high stakes are attached.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, they believe the time they have to prepare students for the CCAA-WL is inadequate, PD efforts have been insufficient to help them understand the measurement properties of the assessments and how to use test data to identify students' writing strengths and needs, and support from administrators to use test data to improve classroom writing instruction is lacking. Our findings comport with other surveys that report negative attitudes toward assessments (Lyons, 2014), often because they are viewed as subtractive rather than additive elements in the education system (also see Loeb, Knapp, & Elfers, 2008), especially when high stakes are attached.…”
Section: Discussionsupporting
confidence: 88%
“…Others contend that the accountability movement with increased competition, autonomy, and choice will not improve the quality of schools and learning, and, indeed, is creating adverse effects, such as narrowing learning, demoralizing teachers, increasing student drop-outs, and loosening integrity among school administrators, teachers and students (McNeil et al 2008). High-stakes testing systems are, according to growing number of researchers, including Au (2007), Berry and Sahlberg (2006), Nichols and Berliner (2007), Loeb et al (2008), and Shirley (2008), narrowing curricula, increasing the practice of presentation-recitation instructional modes, stifling creativity and undermining student engagement in schools. This has led to some civil disobedience.…”
Section: Competition and Test-based Accountabilitymentioning
confidence: 99%
“…Standards-based reform (SBR) presupposes that creating high quality content standards improves teaching and learning by providing consistent and purposeful learning expectations (Smith & O'Day, 1990). There is evidence that standards drive the curriculum in many classrooms (Loeb et al, 2008). Stecher et al (2000; found standardized testing influences curriculum, particularly when there is a lack of alignment between the standards and assessment, teachers may narrow the curriculum to adapt instruction to the test.…”
Section: Tablesmentioning
confidence: 99%
“…National security concerns, economic competitiveness, outdated standards, and mediocre results on national and international standardized assessments are cited as the rationale for overhauling American science education (Mehta, 2013;NGSS Lead States, 2013e). Considerable debate has taken place since the dawn of standards-based reform, as to whether these policies catalyze beneficial change in schools and classrooms (Darling-Hammond, 2004;Desimone, 2013;Diamond, 2007;Loeb, Knapp, & Elfers, 2008). If the NGSS are implemented as the authors intended, changes to classroom practice should be evident and substantial (Pruitt, 2014).…”
Section: Tablesmentioning
confidence: 99%
See 1 more Smart Citation